THE QURANIC CONCEPTION OF JUSTICE AND ITS APPLICATION IN ISLAMIC LEGAL THOUGHT - Taufik Setyaudin; Ethan Tan; Ryan Teo (Yayasan Adra Karima Hubbi, 2026)
Justice constitutes a central principle in the Qur’anic worldview, shaping both ethical conduct and legal reasoning within Islamic thought. Increasing complexity of contemporary legal and social contexts has renewed scholarly interest in how Qur’anic justice can be understood and applied in modern Islamic legal systems. This study aims to examine the conceptual structure of justice in the Qur’an and analyze its application within classical and contemporary Islamic legal thought. A qualitative interpretive design was employed, integrating thematic exegesis of Qur’anic verses with comparative analysis of major Islamic legal schools and contemporary scholarship. Results indicate that Qur’anic justice is articulated through interconnected concepts such as ?adl, qis?, and m?z?n, reflecting moral, procedural, and systemic dimensions. Findings further reveal that Islamic legal traditions operationalize these principles through diverse methodologies, enabling both continuity and adaptability. Contemporary interpretations demonstrate increased emphasis on social justice, human rights, and contextual application. This study concludes that the Qur’anic conception of justice provides a comprehensive and flexible framework capable of guiding Islamic legal thought across different historical and social contexts.